2020
DOI: 10.1039/d0nr05633b
|View full text |Cite
|
Sign up to set email alerts
|

Optically detected magnetic resonance in CdSe/CdMnS nanoplatelets

Abstract: Core/shell CdSe/(Cd,Mn)S colloidal nanoplatelets containing magnetic Mn2+ ions are investigated by the optically detected magnetic resonance technique, combining 60 GHz microwave excitation and photoluminescence detection. Resonant heating of the Mn...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…342 In Mn-doped core/shell NPLs the spin lifetime is found to be on the order of 100 μs at diluted doping levels. 574 Also, it has been demonstrated that dangling surface bonds in NPLs result in surface magnetism due to the localized spins of the dangling bond states behaving as magnetic ions. 379 This final illustration demonstrates the significance of surface control in NPLs for engineering their quantum properties, such as single-photon emission and spintronic.…”
Section: Other Applicationsmentioning
confidence: 99%
“…342 In Mn-doped core/shell NPLs the spin lifetime is found to be on the order of 100 μs at diluted doping levels. 574 Also, it has been demonstrated that dangling surface bonds in NPLs result in surface magnetism due to the localized spins of the dangling bond states behaving as magnetic ions. 379 This final illustration demonstrates the significance of surface control in NPLs for engineering their quantum properties, such as single-photon emission and spintronic.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Two-dimensional colloidal nanoplatelets (NPLs) have a thickness of only several atomic layers but much larger in-plane extensions. , That is, the exciton confinement is extremely strong in the direction perpendicular to the NPL plane, while the in-plane motion is free. CdSe NPLs have remarkable optical properties with narrow emission lines, , low lasing threshold, strong optical gain, , and large multiphoton absorption cross section. , A wide variety of spin phenomena has recently been reported for NPLs. The exciton with its large binding energy dominates the optical properties of CdSe NPLs. Therefore, comprehensive information on the exciton parameters is important.…”
mentioning
confidence: 99%
“…The Mn concentration in the shells is 1% in the sample #1 and 4% in the sample #2. The Mn concentrations were estimated by measuring the spin–lattice relaxation times (see refs and for the method description). In the sample #2, a small concentration of zinc (about 8%) was added to the (Cd,Zn,Mn)S shell.…”
Section: Resultsmentioning
confidence: 99%